Students’ cognitive engagement and academic performance in a flipped classroom model in outstanding class program - Salasiah Ammade; Ali Wira Rahman; Nurhasanah Nurhasanah (JINoP (Jurnal Inovasi Pembelajaran), 2023)
Technology integration has begun to stir the education world particularly when COVID-19 hits the world. One of the popular learning modes during this unstable situation is flipped classroom in which class material is sent earlier to students via communication tools like WhatsApp or Telegram and will be discussed more in an online or offline class meeting. However, the implementation of this learning mode still lacks of research in terms of cognitive engagement and academic performance. In light of this issue, this study aims to research deeply the impact of the flipped classroom on students’ cognitive engagement and their academic performance in learning English particularly writing descriptive text in an outstanding class program. The subject in this research was 18 students of an outstanding class program in a private school in eastern region of Indonesia. Students learning results, observation and questionnaire were used to gather the data needed and then analyzed quantitatively. The findings showed students’ cognitive engagement needs to be encouraged to make them more active and enthusiastic to participate in the learning process. Whilst, the learning result revealed a slight improvement. In conclusion, flipped classroom in an outstanding class program may work well if it is implemented actively by all parties like teachers, students, and parents. We, therefore recommended doing further research on the issue of flipped classroom and learning achievement to enrich the world of education research.